Factors Affecting Chinese Tourists’ Pro-Environmental Intention to Stay at Eco-Friendly Hotels in Thailand - Zong, Ximan; Barnes, John (Journal of Multidisciplinary in Social Sciences, 2023)
The objective of this study was to examine the intentions of Chinese tourists that are related to staying at eco-friendly hotels in Thailand by employing a model combining the Theory of Planned Behavior and the Value-Belief-Norm Theory. In order to investigate the factors that influence the intention of Chinese hotel guests to stay in green hotels, a quantitative research approach was applied for this study with a questionnaire on the eco-friendly and conventional hotels in Bangkok, Nakon Nayok and Phuket completed by a sample of 436 Chinese hotel guests. The results indicate that their sense of obligation to take pro-environmentally friendly actions, attitude towards behavior, subjective norms, and perceived behavioral control have a significant influence on the intention of Chinese guests to stay in eco-friendly hotels while traveling in Thailand. With the use of pro-social and self-interest variables, the proposed model indicates a high level of prediction to the behavioral intention (R2 = 0.455). Recommendations are provided for government institutions in both countries to introduce educational programs to strengthen the environmental awareness of tourists from China and to facilitate the implementation and conducting of hotel operations that are based on the requirements of environmentally aware travelers by hotel managers at eco-friendly hotels in Thailand.